Disseminated fusariosis by Fusarium proliferatum in a patient with aplastic anaemia receiving primary posaconazole prophylaxis - case report and review of the literature - Ricna, Dita; Lengerova, Martina; Palackova, Martina; Hadrabová, Markéta; Kocmanova, Iva; Weinbergerova, Barbora; Pavlovsky, Zdenek; Volfova, Pavlina; Bouchnerova, Jana; Mayer, Jiri; Racil, Zdenek (Mycoses, 2016)
Disseminated fusariosis is a life-threatening, invasive, opportunistic infection in immunocompromised patients, especially those with haematological malignancies. The prognosis is poor because these fungi are resistant to many of the available antifungal agents. We present a case of disseminated fusariosis caused by Fusarium proliferatum in a patient with severe aplastic anaemia complicated by a secondary infection of Aspergillus flavus, with a fatal outcome. We also review the documented Fusarium infections in immunocompromised hosts.
Keywords: triazoly; Male; Fusarium; mladý dospělý; Young Adult; oportunní infekce; Aspergillosis; Triazoles; Fatal Outcome; Opportunistic Infections; Coinfection; mužské pohlaví; Fusariosis; aplastická anemie; Anemia, Aplastic; antifungální látky; koinfekce; Immunocompromised Host; fatální výsledek; Aspergillus flavus; imunokompromitovaný pacient; aspergilóza; lidé; Humans; Antifungal Agents; fusarióza